Effect of proximal balloon edge dilation technique for opening a side branch ostium in repetitive‐proximal optimizing technique sequence. Issue 1 (24th April 2020) - Kume, Teruyoshi; Murasato, Yoshinobu; Yamada, Ryotaro; Koyama, Terumasa; Tamada, Tomoko; Imai, Koichiro; Okamoto, Hiroshi; Enzan, Ayano; Neishi, Yoji; Uemura, Shiro
Abstract: Objective: The purpose of this experimental bench test was to compare stent deformation, obstruction of stent struts at a jailed side branch (SB) ostium, and stent strut malapposition between SB inflation using proximal balloon edge dilation (PBED) technique and SB inflation using conventional balloon dilation in repetitive‐proximal optimizing technique (re‐POT) sequence. Background: The second proximal optimizing technique (POT) procedure in the re‐POT sequence might increase obstruction of stent struts at a jailed SB ostium, because deformation of stent cells at the main branch (MB) occurred during SB inflation for opening the SB ostium. Methods: A fractal coronary bifurcation bench model made of flexible urethane was used, and crossover single‐stent implantation (Xience Sierra, Abbott Vascular, Santa Clara, CA, n = 12) was performed from the MB with the re‐POT sequence. During the re‐POT sequence, the jailing rate at the SB ostium assessed by videoscopy was compared between SB inflation using PBED technique (PBED group, n = 6) and SB inflation using conventional balloon dilation (conventional group, n = 6). Results: The jailing rate after the second POT procedure tended to be lower in the PBED group than in the conventional group (26 ± 12% vs. 34 ± 8%, p = .211), and the change in the jailing rate during the second POT procedure was significantly smaller in the PBED group than in the conventional group (4.8 ± 5.3% vs. 11.6 ± 3.5%, p = .026). Conclusions: In the re‐POT sequence, the PBED technique with a short balloon for SB inflation might minimize worsening of the jailing rate at the SB ostium during the second POT procedure.